Konseling Teman Sebaya Berpasangan dalam Kelompok sebagai Treatmen Masalah Belajar Siswa - Kasobar, Kasobar (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
The exceess number of students foster an effect on the students' personal services in the implementation of counseling. The Research purposes are : 1. To overcome the disadvantages of foster students completed 330 students get optimal care 2. To train by empower students to learn to be independent on the issue effectively in everyday life (KES) is not disturbed. 3. Reduce dependence on supervising teacher student counselor. Research in the Junior High School 1 Kandeman using 2 cycles. Results of cycle 1, suspensions 54.48 learning for enough categories, the score of counseling peer pairs 152. 32 students have completed and 8 students have not completed. Cycle 2, suspensions 72.43 learning for good category, the score of peer counseling peer pairs 193.4. 36 students have completed (90%), and 4 students (10%) have not completed. Who has not completed referrals to counselors